2020
DOI: 10.3390/children7100183
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Assessment and Rehabilitation for Pediatric-Onset Multiple Sclerosis: A Scoping Review

Abstract: Cognitive impairment is increasingly recognized as an important clinical issue in pediatric multiple sclerosis (MS). However, variations regarding its assessment and remediation are noted in clinical arena. This scoping review aims to collate available evidence concerning cognitive assessment tool and cognitive rehabilitation for pediatric MS. We performed a systematic search of electronic databases (MEDLINE, PubMed, CINAHL Plus, and Web of Science) from inception to February 2020. Reference lists of included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Yeh, et al [45] for instance, reported that parents of CAMS perceived the school related performance of their child to be poorer as compared to parents of age-matched healthy controls. Here, mismanagement of time because of fatigue-related symptoms, the negative impact of fatigue on mental health, and lack of knowledge regarding how to manage fatigue-related symptoms were reported by caregivers as some factors leading to poorer school-related performance in CAMS [18,39,57,58]. Moreover, to add towards the burden of MS, a lack of awareness among teachers was reported in some of the studies reviewed [18,29,33,39].…”
Section: Physical and Psychological Impact Of Msmentioning
confidence: 99%
“…Yeh, et al [45] for instance, reported that parents of CAMS perceived the school related performance of their child to be poorer as compared to parents of age-matched healthy controls. Here, mismanagement of time because of fatigue-related symptoms, the negative impact of fatigue on mental health, and lack of knowledge regarding how to manage fatigue-related symptoms were reported by caregivers as some factors leading to poorer school-related performance in CAMS [18,39,57,58]. Moreover, to add towards the burden of MS, a lack of awareness among teachers was reported in some of the studies reviewed [18,29,33,39].…”
Section: Physical and Psychological Impact Of Msmentioning
confidence: 99%